Indexing Byzantine Cypriot coinage, using image analysis - Neophytou, A.; Lanitis, Andreas (My University, 1997)
A relational database containing information and pictures of all coins produced in a country, can be an invaluable source of information for researchers working in disciplines like history, archeology and numismatic studies. This paper presents one of the first attempts to index coins from a coin database with the help of an image processing search engine. In particular we describe coin image retrieval based on coin shapes, sizes and according to the structures appearing in coins. For our preliminary experiments we used a database containing images of Byzantine coins produced in Cyprus.
Keywords: Coins; Byzantine coins